Strand Orientation Bias Detector to determine the probability of FFPE sequencing artifacts. Issue 6 (20th May 2021) - Diossy, Miklos; Sztupinszki, Zsofia; Krzystanek, Marcin; Borcsok, Judit; Eklund, Aron C; Csabai, István; Pedersen, Anders Gorm; Szallasi, Zoltan
Abstract: Formalin-fixed paraffin-embedded tissue, the most common tissue specimen stored in clinical practice, presents challenges in the analysis due to formalin-induced artifacts. Here, we present Strand Orientation Bias Detector (SOBDetector), a flexible computational platform compatible with all the common somatic SNV-calling pipelines, designed to assess the probability whether a given detected mutation is an artifact. The underlying predictor mechanism is based on the posterior distribution of a Bayesian logistic regression model trained on The Cancer Genome Atlas whole exomes. SOBDetector is a freely available cross-platform program, implemented in Java 1.8.